District Practices Associated With Successful SWPBIS Implementation. (May 2018) - George, Heather Peshak; Cox, Karen Elfner; Minch, Devon; Sandomierski, Therese
Schoolwide positive behavior interventions and supports (SWPBIS) is a widely implemented model for systematically supporting the social and behavioral development of students with and without disabilities, including those with and at risk for emotional and behavioral disorders. Identifying district factors associated with SWPBIS implementation fidelity and improved student outcomes can assist district personnel with appropriate allocation of resources, including professional development and school-based implementation support. Due to the limited empirical support for district-level factors that influence school practices and student outcomes, this exploratory study was conducted with the goal of identifying characteristics associated with school districts that have a high proportion of schools implementing SWPBIS with fidelity and sustained positive student discipline outcomes. Six high-implementing districts were identified, and semi-structured interviews with district staff were then conducted to identify common features staff attributed to their district's positive outcomes. Analysis of those interviews revealed eight themes including District Coordinator, Coaches, District Teaming, Internal Implementation Drivers, Leadership Buy-In and Support, District Data Infrastructure, Direct Support to Schools, and Communication. Limitations and implications are discussed.